THE LEGAL CAPACITY TO TRADE - ADELIN UNGUREANU (Annals of the University of Petrosani: Economics)
Trading is a part of our society. The man has been trading from ancient times so the amount of trades and transactions around the world is huge. In order for us to initiate, organize and deploy such trades we have to have certain rules which can help regulate the social and professional or legal aspect of trades. Therefore the sole trader capacity must be obtained and used in order for the contracts to be valid. The right and obligations that come with this capacity constitute activities that can be reflected and analysed by obtaining and maintain the sole trader status.